Role of the Type VI Secretion System in the Pathogenicity of Pseudomonas syringae pv. actinidiae, the Causative Agent of Kiwifruit Bacterial Canker - Wang, Nana; Han, Ning; Tian, Runze; Chen, Jiliang; Gao, Xiaoning; Wu, Zhiran; Liu, Yuqi; Huang, Lili (Frontiers in Microbiology, 2021)
The Type VI secretion system (T6SS) is a class of macromolecular machine that is required for the virulence of gram-negative bacteria. However, it is still not clear what the role of T6SS in the virulence of Kiwifruit bacterial canker pathogen Pseudomonas syringae pv. actinidiae (Psa) is. Here, we found a T6SS gene cluster consists of 13 core genes (A-J) in the genome of Psa M228 based on a genome-wide analysis. To determine whether Psa M228 produces a functioning T6SS, we selected tssM and tssJ genes present in the T6SS gene cluster for mutational analyses. Western blot results showed that the tssM and tssJ genes were necessary for Hcp secretion, thus indicating that the T6SS gene cluster encodes a functioning T6SS. We present evidence that T6SS plays an important role in the pathogenicity of Psa M228. We also investigated the role of the T6SS system in bacterial competition, colonization, biofilm formation, hydrogen peroxide tolerance and proteolytic ability. All these properties of the two genes complementation mutants were restored to the same level as the wild-type strain M228. Quantitative real-time results showed that during the interaction between the deletion mutant M228ΔT6SS and the host, the expression levels of the T3SS transcriptional regulatory genes hrpR and hrpL, structural genes hrpC and hopP1, and effector genes hopM1 and hopH1 were all down-regulated at different levels. Taken together, our data provide the first evidence demonstrating that the T6SS system plays an important role in the virulenc of Psa, probably due to T6SS affecting bacterial competition, colonization, biofilm formation and environmental adaptability. Moreover we found that there is a complicated relationship between T6SS with T3SS.